2011
DOI: 10.1016/j.ijhydene.2010.10.093
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic irradiation on hydrolysis of magnesium hydride to enhance hydrogen generation

Abstract: Abstract:This paper describes the ultrasonic irradiation on the hydrolysis of magnesium hydride to enhance hydrogen generation; the effects of the ultrasonic frequency and the sample size on the hydrogen generation were mainly examined. In the experiments, three MgH 2 particle and nanofiber samples were soaked in distilled water and ultrasonically irradiated at frequencies of 28, 45, and 100 kHz. Then, the amount of hydrogen generated was measured. We found that the low frequency of ultrasonic irradiation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Kushch et al have demonstrated that hydrogen generation is improved via the interaction of magnesium with organic acids [12]. Ultrasonic irradiation was also considerably effective in improving the hydrolysis of MgH 2 [13]. Grosjean et al [14e16] showed that ball milling of pure mag nesium has no effect on the Mg reactivity for hydrolysis in pure water.…”
Section: Introductionmentioning
confidence: 99%
“…Kushch et al have demonstrated that hydrogen generation is improved via the interaction of magnesium with organic acids [12]. Ultrasonic irradiation was also considerably effective in improving the hydrolysis of MgH 2 [13]. Grosjean et al [14e16] showed that ball milling of pure mag nesium has no effect on the Mg reactivity for hydrolysis in pure water.…”
Section: Introductionmentioning
confidence: 99%
“…The need for compact, safe, and inexpensive hydrogen sources is a key issue for the development of fuel cells. One of the most attractive metal hydrides for hydrogen generation is magnesium hydride, (MgH 2 ) [7][8][9][10][11][12][13][14][15][16][17]. It is an especially promising material owing to its quite high hydrogen capacity of 7.6 mass% and relatively low production cost.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic irradiation has also been used to facilitate the generation of hydrogen from MgH 2 during hydrolysis, i. e. MgH 2 +H 2 O→Mg(OH) 2 +2H 2 . The fast generation of fresh surfaces due to particles’ collisions increased the reaction rate by 15 folds as compared to a non‐sonicated MgH 2 powder. In this case ∼ 5.2 wt % H 2 was released in just two hours.…”
Section: Non‐thermal and Non‐straightforward Thermally Driven Methodsmentioning
confidence: 99%